2003
DOI: 10.1034/j.1600-079x.2003.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Author index

Abstract: Our previous work showed that melatonin (N-acetyl-5-methoxytryptamine) inhibits proliferation of the human endometrial cancer cell line, Ishikawa, which is estrogen receptor-positive. The aim of the present study was to determine whether Ishikawa cells possess membrane melatonin receptors. Binding of the radioligand 2-[125I]-iodomelatonin to membrane preparations obtained from Ishikawa cells was detectable, saturable and stable. Scatchard analysis revealed that the dissociation constant (Kd) of the binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…The expression of these receptors is up-regulated by the melatonin treatment and is associated with the down-regulation of the ER-beta and PRB (Chuffa et al, 2011). Influence of the melatonin on the incidence of endometrial cancer has been suggested (Sandyk et al, 1992) and the presence of the functional MT2 receptor was detected in the estrogen positive cell line derived from patient with endometrial carcinoma (Kobayashi et al, 2003). …”
Section: Melatonin Receptors In the Reproductive And Gestational Tmentioning
confidence: 99%
“…The expression of these receptors is up-regulated by the melatonin treatment and is associated with the down-regulation of the ER-beta and PRB (Chuffa et al, 2011). Influence of the melatonin on the incidence of endometrial cancer has been suggested (Sandyk et al, 1992) and the presence of the functional MT2 receptor was detected in the estrogen positive cell line derived from patient with endometrial carcinoma (Kobayashi et al, 2003). …”
Section: Melatonin Receptors In the Reproductive And Gestational Tmentioning
confidence: 99%
“…An MT2 melatonin receptor subtype that may mediate the cancer-protective effect of melatonin has been described in a human endometrial cancer cell line (15,16). This report presents the first evaluation of the relationship between night work and endometrial cancer risk in a large prospective cohort of pre-and postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin has also showed to suppress tumor growth in a number of experimental models, including undifferentiated neoplasms, sarcomas and carcinomas, such as squamous cell cervical carcinomas, prostate cancer, endometrial cancer, colon cancer, trophoblastoma, choriocarcinoma, neuroblastoma, hepatocarcinoma, ovarian carcinoma, melanoma and mammary carcinoma [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Melatonin has been given to patients with solid tumors for many years with inconsistent results.…”
Section: Introductionmentioning
confidence: 99%